Triune Elohim - Merkle, B; Benjamin R Merkle (2012)
In 1563, the publication of the Heidelberg Catechism marked the conversion of the Rhineland Palatinate to a stronghold for Reformed religion. Immediately thereafter, however, the Palatinate church experienced a deeply unsettling surge in the popularity of antitrinitarianism. To their Lutheran and Catholic opponents, this development revealed a toxic connection between Reformed theology and the tenets of antitrinitarianism. As early as 1565, for instance, the Catholic Cardinal Stanislaus Hosius argued anonymously that the Reformed principle of sola scriptura was indistinguishable from the biblicism which had led heretics to reject the doctrine of the Trinity on the grounds that it was nowhere explicitly justified in the biblical text. Seven years later, the displaced Italian theologian and Heidelberg professor, Girolamo Zanchi, countered this argument in his De Tribus Elohim (1572). This huge landmark of this early theological crisis in Heidelberg sought to oppose the biblicism of the early antitrinitarians by arguing that the doctrine of the Trinity was explicitly taught within the Hebrew divine names Jehovah and Elohim. The following year De Tribus Elohim received an Imperial Privilege from the Catholic court in Vienna, a distinction virtually unheard of for a Reformed theological text. Zanchi’s argument was then widely promulgated in the marginal notations of the tremendously influential Biblia Sacra of Franciscus Junius and Immanuel Tremellius, and became a staple of refutations of antitrinitarianism thereafter. Yet Zanchi’s confidence that trinitarian theology was contained within the Hebrew of the Old Testament was not shared by many of his own Reformed colleagues. John Calvin’s exegetical works had explicitly rejected this argument; and theologians like David Pareus (Zanchi’s younger colleague in Heidelberg) and the Dutch Hebraist Johannes Drusius preferred a more historical-grammatical reading of the Old Testament and dismissed Zanchi’s reading of the name Elohim despite the danger that this might sacrifice a valuable defence against antitrinitarianism. Complicating the picture further, the Lutheran polemicist Aegidius Hunnius directed Zanchi’s arguments against Calvin in his Calvinus Iudaizans (1593). This variety of responses to Zanchi’s argument demonstrates the diversity of assumptions about the nature of the biblical text within the Reformed church, contradicting the notion that the Reformed world in the age of “confessionalization” was becoming increasingly homogenous or that the works of John Calvin had become the authoritative touchstone of Reformed orthodoxy in this period.